Repeat film analysis and its implications for quality assurance in diagnostic radiology: An institutional case study - Nittayasupaporn, Bunchai; Proukkerd, Jatupong; Permwong, Manassawee; Tippayamontri, Thititip (The Thai Journal of Radiological Technology, 2024)
The primary objective of this research was to analyze the rate of repeated chest examinations using the Reject and Usage Analysis tool program of the Samsung XGEO-GC80 X-ray machine. A retrospective study was conducted at King Chulalongkorn Memorial Hospital (KCMH) in the Department of Radiological Diagnostic. The study involved collecting statistics and closely examining the causes behind rejected images within the machine system. Among the key findings were Chest examinations accounted for the highest number of images, comprising 39.32% of the total 40,400 images. Repeated images were most prevalent in chest examinations, making up 32.21%of the 7,550 rejected images and 6.02% of all images. The primary reason for rejecting images was improper positioning, constituting 75.47% of all rejected images. In chest examinations, the most common reason for image rejection was improper breathing, contributing to 54.3% of all 1,321rejected images and 14.0% of all rejected images in the study. Furthermore, the study highlighted that a significant portion of X-ray image rejections resulted from human errors, primarily from radiological technologists. To reduce the rate of repeated imaging, the following recommendations were proposed for i) comprehensive evaluation of the patient's condition before the X-ray examination, ii) Ensuring proper patient positioning, iii) Implementation of various initiatives within the healthcare unit, including regular training for radiologists, and iv) Establishment of criteria for accepting radiographic images across all radiological technologists within the diagnostic department. In conclusion, these analyses are essential to enhance the quality of radiological services at KCMH, minimize image rejections, and ultimately improve patient care and radiation safety.